The Historical Construction of National Consciousness : Selected Writings - Szűcs, Jenő (Book collections on Project MUSE., 2022)
"A short essay entitled Three Historical Regions of Europe, appearing first in a samizdat volume in Budapest in 1980, instantly put its author into the forefront of the transnational debate on Central Europe, alongside such intellectual luminaries as Milan Kundera and Czesław Miłosz. The present volume offers English-language readers a rich selection of the depth and breadth of the legacy of Jenő Szűcs (1928-1988). The selection documents Szűcs's seminal contribution to many contemporary debates in historical anthropology, nationalism studies, and conceptual history. It contains his key texts on the history of national consciousness and patterns of collective identity, as well as medieval and early modern political thought. The works published here, most of them previously unavailable in English, provide a sophisticated analysis of a wide range of subjects from the myths of origins of Hungarians before Christianization to the political and religious ideology of the Dózsa peasant uprising in 1514, the medieval roots of civil society, or the revival of ethnic nationalism during the communist era. The volume, with an introduction by the editors locating Szűcs in a transnational context, offers a unique insight into the complex and sensitive debate on national identity in post-1945 East Central Europe"--